On‐POM Ring‐Opening Polymerisation of N‐Carboxyanhydrides. (19th January 2021) - Soria‐Carrera, Héctor; Franco‐Castillo, Isabel; Romero, Pilar; Martín, Santiago; de la Fuente, Jesús M.; Mitchell, Scott G.; Martín‐Rapún, Rafael
Abstract: The ring‐opening polymerisation of α‐amino acid N ‐carboxyanhydrides (NCAs) offers a simple and scalable route to polypeptides with predicted and narrow molecular weight distributions. Here we show how polyoxometalates (POMs)—redox‐active molecular metal‐oxide anions—can serve as inorganic scaffold initiators for such NCA polymerisations. This "On‐POM polymerisation" strategy serves as an innovative platform to design hybrid materials with additive or synergistic properties stemming from the inorganic and polypeptide component parts. We have used this synthetic approach to synthesise a library of bactericidal poly(lysine)–POM hybrid derivatives that can be used to prevent biofilm formation. This versatile "On‐POM polymerisation" method provides a flexible synthetic approach for combining inorganic scaffolds with amino acids, and the potential to tailor and improve the specificity and performance of hybrid antimicrobial materials. Abstract : On‐POM polymerisation: An amino‐functionalised polyoxometalate (POM) acts as initiator for the ring‐opening polymerisation (ROP) of α‐amino acid N ‐carboxyanhydrides (NCAs) under living polymerisation conditions. The resulting POM–peptide materials (POMlymers) possess bactericidal properties and prevent biofilm formation.